NILAI TAMBAH INDUSTRI PENGOLAHAN KAYU JA TI PERUM PERHUTANI UNIT I JAWATENGAH - Hendro Prahasto; Boen M Purnama (Jurnal Penelitian Hasil Hutan, 1994)
The export tariff  policy on sawntimher is aimed at accelerating the development of  high volue-added  industry. Study on the valu- added of  teak processing industry belongs to the State  Forestry Company (Perum Perhutani)   is focused on  sawntimber. and  woodworking  products  such as doors, windows, frames, decking and parquets.Study  result shows  that  not  all sawmill plants provided positive value added.  in aggregate, sawntimber  industry yields  value  added  of  Rps. 55, 542  per cu. m or 11 percent of processed  raw   material value.  Wood working industry yielded a higher  value  added,  Rps.1,023, 791 per cu. m or almost  half  of  its  raw  material  value